Sulfur positive electrode for lithium-sulfur battery, lithium-sulfur battery and preparation method of sulfur positive electrode

By using a combination of sulfur positive electrode covered with an active lithium film and a lithium-free negative electrode in lithium-sulfur batteries, the problem of short battery cycle life caused by metal lithium negative electrodes is solved, and a longer battery life and higher energy density are achieved.

CN119480882APending Publication Date: 2025-02-18CHINA ENERGY LITHIUM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310989490.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The use of metal lithium negative electrodes in existing lithium sulfur batteries has problems such as soft quality and no support, high usage, dendrite and volume expansion, resulting in short battery cycle life.

Method used

A sulfur positive electrode covered with an active lithium film is used as the lithium source, and a lithium-free negative electrode with stable properties is used to form a short-chain polysulfide Li2Sx by reacting active lithium with active sulfur in the sulfur positive electrode, which is adsorbed onto the carbonaceous support material.

Benefits of technology

The safety hazards of using metal lithium negative electrodes are avoided, the service life of the negative electrodes is extended, and the circulation life of lithium sulfur batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480882A_ABST
    Figure CN119480882A_ABST
Patent Text Reader

Abstract

The invention provides a sulfur positive electrode for a lithium-sulfur battery, the lithium-sulfur battery and a preparation method of the lithium-sulfur battery. The sulfur positive electrode for the lithium-sulfur battery comprises a sulfur positive electrode membrane and an active lithium membrane covering the sulfur positive electrode membrane, and the mass of active lithium in the active lithium membrane is 10%-45% of the mass of active sulfur in the sulfur positive electrode membrane. The lithium-sulfur battery comprises the sulfur positive electrode and a lithium-free negative electrode, active lithium in the active lithium membrane reacts with active sulfur in the sulfur positive electrode membrane to form Li2Sx, and x is smaller than or equal to 4. According to the lithium-sulfur battery, potential safety hazards caused by the use of a metal lithium negative electrode are avoided; in addition, the lithium-sulfur battery can adopt various lithium-free materials or foil materials as the negative electrode, the negative electrode is stable and reliable relative to metal lithium, and the cycle life of the battery is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a lithium-sulfur battery. Background Art

[0002] With the rapid development of lithium batteries, the energy density of lithium-ion batteries has approached its theoretical value, and it is urgent to develop the next generation of high energy density battery systems. Lithium-sulfur batteries have always been a hot topic of research due to their high energy density (up to 500Wh / kg or more).

[0003] Normally, there is no active lithium in the positive electrode of lithium-sulfur batteries, so metallic lithium is generally used as the negative electrode. Since metallic lithium is soft and unsupported, the thickness of lithium strips needs to be increased to achieve battery assembly, and the amount used will be more than the actual demand. In addition, a series of problems with metallic lithium negative electrodes (dendrites, volume expansion, etc.) can also lead to the failure of metallic lithium negative electrodes and short battery cycle life.

[0004] In summary, it is indeed necessary to provide a lithium-sulfur battery that avoids the use of metallic lithium negative electrode and can achieve long cycle. Summary of the invention

[0005] The present invention provides a lithium-sulfur battery, which does not use a metallic lithium negative electrode, but instead provides a lithium source through a sulfur positive electrode covered with an active lithium film to achieve battery circulation; in addition, the lithium-sulfur battery uses a stable lithium-free negative electrode, which can greatly extend the service life of the negative electrode, thereby improving the cycle life of the lithium-sulfur battery.

[0006] In order to achieve the above objectives, in a first aspect, the present invention provides a sulfur positive electrode for a lithium-sulfur battery, characterized in that the sulfur positive electrode comprises a sulfur positive electrode membrane and an active lithium film covering the sulfur positive electrode membrane, wherein the mass of active lithium in the active lithium film is 10%-45% of the mass of active sulfur in the sulfur positive electrode membrane.

[0007] In some embodiments, the active sulfur in the sulfur positive electrode membrane is elemental sulfur, sulfurized polyacrylonitrile and a combination thereof.

[0008] In some embodiments, the sulfur positive electrode membrane further includes a surface-treated carbonaceous carrier material, the carbonaceous carrier material is carbon nanotubes, graphene, ordered mesoporous carbon, transition metal carbide and a combination thereof, and the surface of the surface-treated carbonaceous carrier material has at least one of the following chemical bonds: CN, CO, CB, CP, CS, CM (M is a metal element, including at least one of Li, Na, Mg, Al, Fe, Ti, K, Ca, Cr, Mn, Co, Ni, Cu, Zn, Zr, Mo, Ag, In, Sn, Au, Pt, W, Pb, Ge), CF, C-Cl, C-Br, CI. These heterogeneous atoms provide adsorption sites and catalytic sites for lithium polysulfide, catalyzing the conversion of long-chain lithium polysulfide into short-chain Li2S x , where x is less than or equal to 4.

[0009] In some embodiments, the active lithium film is a metallic lithium film having a thickness of 1 micrometer to 50 micrometers.

[0010] In some embodiments, the metallic lithium film has through pores, and a porosity of 1% to 85%.

[0011] In a second aspect, the present invention provides a lithium-sulfur battery comprising the sulfur positive electrode, a lithium-free negative electrode and an electrolyte, wherein the active lithium in the active lithium film reacts with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.

[0012] In some embodiments, the sulfur cathode film includes a surface-treated carbonaceous carrier material, the Li2S x adsorbed on the carbonaceous support material.

[0013] In some embodiments, the lithium-free negative electrode includes a graphite negative electrode, a silicon-carbon negative electrode, or a silicon-oxygen negative electrode.

[0014] In some embodiments, the electrolyte includes a liquid electrolyte and a combination of a liquid electrolyte and a solid electrolyte.

[0015] The liquid electrolyte comprises a solvent, a lithium salt and optional additives,

[0016] The solvent is a carbonate solvent and an ether solvent, and an ether solvent is preferred.

[0017] The lithium salt is at least one of LiPF6 (lithium hexafluorophosphate) (the most common lithium salt at present), LiBF4 (lithium tetrafluoroborate), LiBOB (lithium dioxalatoborate), LiDFOB (lithium difluoroborate oxalate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethylsulfonyl)imide), LiPF2O2 (lithium difluorophosphate) and LiDTI (lithium 4,5-dicyano-2-trifluoromethylimidazole).

[0018] Additives include film formers (vinyl carbonate, cyanoacrylate, sulfur dioxide, carbon disulfide, fluoroethylene carbonate, etc.), flame retardant additives (trimethylolpropane, triphenyl phosphate, trifluoropropylene, tri(trifluoroethyl) phosphate, etc.), and charging protective agents (benzyl alcohol, triethylenediamine, etc.).

[0019] Solid electrolytes include sulfide solid electrolytes, oxide solid electrolytes, organic solid electrolytes, and organic-inorganic composite solid electrolytes.

[0020] In a third aspect, the present invention provides a method for preparing the above-mentioned lithium-sulfur battery, comprising:

[0021] Step 1: prepare a mixture of a sulfur positive electrode active material (active sulfur) and a surface-treated carbonaceous carrier material.

[0022] Step 2: uniformly mix the above mixture with a binder, and optionally add a solvent.

[0023] Step 3: Load the mixture obtained in step 2 on the surface of the current collector to obtain a sulfur-containing positive electrode membrane.

[0024] Step 4: Loading the active lithium film on the sulfur positive electrode film to obtain a sulfur positive electrode covered with active lithium.

[0025] Step 5: Assemble the sulfur positive electrode covered with active lithium, the lithium-free negative electrode, the electrolyte, the separator / solid electrolyte and the packaging materials into a lithium-sulfur battery.

[0026] In some embodiments, the mixing in step 1 is carried out above the melting point of sulfur (112°C).

[0027] In some embodiments, the active lithium film in step 4 is supported on the sulfur cathode film by at least one method selected from the group consisting of coating, rolling, physical vapor deposition, and magnetron sputtering.

[0028] In some embodiments, the method further comprises reacting the active lithium in the active lithium film with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.

[0029] In some embodiments, the method further comprises a formation step after step 5, wherein the formation step can be performed at a constant voltage until the current is less than 0.005C. The formation step promotes the Li2S x Formation and its adsorption on carbonaceous support materials.

[0030] In some embodiments, the surface-treated carbonaceous carrier material described in step 1 is prepared by any one of the following methods: surface defect treatment of carbonaceous material, mainly using high-temperature chemical corrosion to connect impurity atoms to the surface of the carbonaceous carrier material, such as sintering the carbonaceous carrier material at high temperature, using nitrogen as a protective gas, and forming CN bonds at the defect positions of the carbonaceous carrier material. In addition to gas, solid substances can also be mixed with carbonaceous carrier materials and then sintered at high temperature, such as sodium carbonate reacting with carbon to form C-Na bonds.

[0031] The lithium-sulfur battery of the present invention has at least the following advantages:

[0032] 1. The lithium-sulfur battery of the present invention avoids using metallic lithium as the negative electrode in the lithium-sulfur battery, thereby avoiding the potential safety hazards caused by metallic lithium during use;

[0033] 2. The lithium-sulfur battery can use a variety of lithium-free materials or foil materials as the negative electrode. The negative electrode is stable and reliable relative to metallic lithium, and the battery cycle life is long.

[0034] 3. Active lithium and active sulfur in the sulfur positive electrode form short-chain polysulfide Li2S x , x is less than or equal to 4, this short-chain polysulfide can be easily adsorbed on the carbonaceous carrier material, and the heterogeneous atoms (including N, O, B, P, S, metal atoms, etc.) on the surface of the carbonaceous material provide affinity sites for the short-chain polysulfide molecules. Through the action of chemical bonds, the short-chain polysulfide on the surface of the carbonaceous carrier material can not only prevent the "sulfur shuttling" problem of lithium polysulfide, but also solve the problem of poor conductivity of active sulfur in the sulfide positive electrode and few active sites for reaction with metallic lithium. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the sulfur positive electrode structure of the present invention;

[0036] Figure 2 This is a scanning electron microscope photograph of the sulfur positive electrode after formation in Example 1;

[0037] Figure 3 The voltage and specific capacity curves of the assembled batteries of Example 1 and Comparative Example 1 during the first charge and discharge;

[0038] Figure 4 The cycle number and discharge capacity curves of the assembled batteries of Example 1 and Comparative Example 1.

[0039] 1 Current collector 2 Active lithium film 3 Surface treated carbonaceous support material 4 Sulfur positive electrode DETAILED DESCRIPTION

[0040] The content of the present invention will be described below in conjunction with the accompanying drawings. For the purpose of clear description, many details will be described together in the following description. However, it should be understood that these details should not be used to limit the present invention. In addition, to simplify the drawings, some known conventional structures and elements will be illustrated in a simple schematic manner in the drawings. The "about", "approximately" or "roughly" used herein is used to modify any slightly variable quantity, but this slight change does not change its essence. If not otherwise specified, the error range of the modified numerical value represented by "about", "approximately" or "roughly" is generally within the allowable range, preferably within 10%, and more preferably within 5%.

[0041] The structural schematic diagram of a sulfur positive electrode of the present invention is as follows Figure 1 shown.

[0042] The sulfur positive electrode of the present invention comprises a current collector 1 and a sulfur positive electrode 4 covered with an active lithium film 2 attached to the current collector 1, wherein the active material in the sulfur positive electrode is adsorbed on a surface-treated carbonaceous carrier material 3. The mass of the active lithium in the active lithium film 2 is 10%-45% of the mass of the active sulfur in the sulfur positive electrode. The active material in the sulfur positive electrode is elemental sulfur, sulfide polyacrylonitrile and a combination thereof. The active lithium can form Li2Sx with the active sulfur in the sulfide positive electrode, wherein the value of x is less than or equal to 4, and the purpose is to form short-chain polysulfides, which can be easily adsorbed on carbonaceous carrier materials with large specific surface areas, and these carbonaceous carrier materials include but are not limited to carbon nanotubes, graphene, ordered mesoporous carbon, transition metal carbides and a combination thereof. In addition, short-chain polysulfides have a small overall molecular weight and very little steric hindrance. They can be displaced on the surface of the material under the guidance of van der Waals forces, and the heterogeneous atoms on the surface of carbonaceous materials (including N, O, B, P, S, metal atoms, etc.) provide affinity sites for short-chain polysulfide molecules. Through the action of chemical bonds, short-chain polysulfides on the surface of carbonaceous carrier materials can prevent the "sulfur shuttling" problem of lithium polysulfide and solve the problem of poor conductivity of active sulfur in the sulfide positive electrode and few active sites for reaction with metallic lithium.

[0043] Usually, lithium-sulfur batteries are matched with metal lithium negative electrodes, but the lithium-sulfur battery of the present invention avoids using metal lithium negative electrodes, and instead uses lithium-free negative electrodes, including graphite negative electrodes, silicon-carbon negative electrodes, and silicon-oxygen negative electrodes. These negative electrodes are more stable than metal lithium negative electrodes, and will not form lithium dendrites. The service life of the negative electrode is no longer a shortcoming that limits the service life of lithium-sulfur batteries.

[0044] The lithium-sulfur battery prepared by combining the above-mentioned sulfur positive electrode covered with an active lithium film with a lithium-free negative electrode with stable performance has a cycle life that is significantly better than the traditional lithium-sulfur battery using a metallic lithium negative electrode.

[0045] In the process of preparing the sulfur positive electrode, an active lithium film with a thickness of 1 micron to 50 microns is used to cover the surface of the sulfur positive electrode. The thickness of the active lithium film is selected according to the mass of the active sulfur in the sulfur positive electrode, which can effectively control the overall molecular weight of polysulfides in the sulfur positive electrode. In addition, in order to better realize the in-situ and controllable generation of short-chain polysulfides, the active lithium film selects a lithium film with through holes, and the porosity ranges from 1% to 85%. After the battery is filled with liquid, the lithium film with through holes can achieve a rapid and large-scale reaction with the active sulfur in the sulfur positive electrode to generate short-chain lithium polysulfides.

[0046] The electrolytes that can be used in the lithium-sulfur battery of the present invention include liquid electrolytes, solid electrolytes and combinations thereof. The liquid electrolyte includes solvents, lithium salts and additives, and the solvents are carbonate solvents and ether solvents, preferably ether solvents. The lithium salt is LiPF6 (lithium hexafluorophosphate), which is the most common lithium salt at present, and at least one of LiBF4 (lithium tetrafluoroborate), LiBOB (lithium dioxalate borate), LiDFOB (lithium difluoroborate oxalate), LiFSI (lithium bis(trifluoromethylsulfonyl)imide), LiTFSI (lithium bis(trifluoromethylsulfonyl)imide), LiPF2O2 (lithium difluorophosphate) and LiDTI (lithium 4,5-dicyano-2-trifluoromethylimidazole).

[0047] In addition, additives can be introduced into the electrolyte of the lithium-sulfur battery to improve the overall performance of the lithium-sulfur battery and its adaptability to different application scenarios. The additives include film-forming agents (vinyl carbonate, acrylic nitrile, sulfur dioxide, carbon disulfide, fluoroethylene carbonate, etc.), flame retardant additives (trimethylolpropane, triphenyl phosphate, trifluoropropylene, tris(trifluoroethyl) phosphate, etc.), and charging protective agents (benzyl alcohol, triethylenediamine, etc.).

[0048] The sulfur positive electrode and the lithium-free negative electrode of the lithium-sulfur battery can be adapted to solid electrolytes at the same time, wherein the solid electrolyte can be selected from at least one of sulfide solid electrolytes, oxide solid electrolytes, organic solid electrolytes, and organic-inorganic composite solid electrolytes.

[0049] The preparation method of the lithium-sulfur battery of the present invention is simple, and the preparation method comprises the following steps:

[0050] Step 1: Prepare a mixture of sulfur positive electrode active material (activated sulfur) and carbonaceous carrier material.

[0051] Step 2: Evenly mix the above mixture with a binder, and a solvent may be used.

[0052] Step 3: Load the mixture obtained in step 2 on the surface of the current collector to obtain a sulfur positive electrode membrane.

[0053] Step 4: Loading the active lithium film on the sulfur positive electrode film to obtain a sulfur positive electrode covered with active lithium.

[0054] Step 5: Assemble the sulfur positive electrode covered with active lithium with the lithium-free negative electrode, electrolyte, separator and packaging materials to prepare a lithium-sulfur battery.

[0055] Wherein, the active lithium film described in step 4 is loaded on the sulfide positive electrode film by at least one method of coating, rolling, physical vapor deposition, and magnetron sputtering.

[0056] Example 1

[0057] Preparation of sulfur cathode covered with active lithium film

[0058] The carbon nanotubes were placed in a tubular furnace, nitrogen was introduced as a protective atmosphere, and the carbon nanotubes were treated at 800°C.

[0059] Elemental sulfur (Aladdin) and surface-treated carbon nanotubes (Shandong Dazhan) were uniformly mixed in a ball mill at a mass ratio of 3:5 for 24 hours. After being evenly mixed, a binder polyethylene terephthalate (without using a solvent) was added, and fiberization treatment was performed at 150°C. The mixture was extruded onto a stainless steel foil and rolled to prepare a sulfur positive electrode membrane.

[0060] A 5-micron-thick active lithium film (Tianjin Zhongneng Lithium Industry Co., Ltd.) was attached to the surface of the above-mentioned sulfur positive electrode film, and a pressure of 3MPa was applied for compaction treatment. The compaction treatment time was 4 hours at a temperature of 45°C, and finally a sulfur positive electrode covered with an active lithium film was obtained. Among them, the mass ratio of active lithium to active sulfur was 7:48, and the mass of active lithium in the active lithium film was 14.5% of the mass of active sulfur in the sulfur positive electrode film.

[0061] Preparation of graphite anode

[0062] The graphite negative electrode, the binder and the conductive agent were dispersed in deionized water in a mass ratio of 95:2:3, and the graphite negative electrode with a thickness of 50 microns was prepared by homogenization and coating.

[0063] The above-mentioned sulfur positive electrode covered with active lithium film and graphite negative electrode are assembled into soft-pack batteries using Z-shaped stacking process, and the full battery is assembled using PP separator and ether electrolyte. The assembled full battery is formed, and then the charge and discharge cycle test is carried out. The conditions of the formation step include: constant voltage charging, the voltage is constant at 2.05V, and the formation is completed after the current is less than 0.005C. The test procedure is as follows: charge with a current of 10mAh and a cut-off voltage of 3V, then discharge with a current of 10mAh and a discharge cut-off voltage of 1.7V, and record the number of battery cycles and the discharge capacity of the battery. The microscopic morphology of the sulfur positive electrode after formation is as follows Figure 2 As shown, the short-chain lithium polysulfides formed after formation are dispersed on the surface of carbon nanotubes in the form of discrete / agglomerated particles.

[0064] Example 2

[0065] Specific implementation method As in Example 1, no diaphragm is used, and ether electrolyte and oxide solid electrolyte sheet (Shenzhen Kejing) are used as ion conductive medium.

[0066] Example 3

[0067] Specific implementation method As in Example 1, only the thickness of the active lithium film is changed to 15 microns. At this time, the mass of active lithium in the active lithium film is 43.5% of the mass of active sulfur in the sulfur positive electrode film.

[0068] Comparative Example 1

[0069] Specific implementation method As in Example 1, only the graphite negative electrode is changed to a pure metal lithium foil with a thickness of 50 microns (Tianjin Zhongneng Lithium Industry Co., Ltd.).

[0070] Figure 3 3 are curves of voltage and specific capacity during the first charge and discharge of the assembled batteries of Example 1 and Comparative Example 1. It can be seen from the figure that the first charging capacity of the assembled batteries of Example 1 and Comparative Example 1 is 197 mAh / g, and the specific capacity comes from the active lithium in the positive electrode. The first discharge capacity of the assembled battery of Example 1 is 169 mAh / g, which is lower than the discharge capacity of the assembled battery of Comparative Example 1 of 178 mAh / g. This is because Example 1 adopts a lithium-free negative electrode, while Comparative Example 1 adopts a pure metallic lithium negative electrode. During the discharge process, the metallic lithium in Comparative Example 1 can provide a part of the lithium source back to the sulfur positive electrode, resulting in a slightly larger discharge capacity than Example 1.

[0071] Figure 4The cycle times and discharge capacity curves of the assembled batteries of Example 1 and Comparative Example 1 are shown. As can be seen from the figure, the battery discharge capacity continues to increase in the first 20 weeks of the battery cycle. This is because as the cycle proceeds, the active lithium gradually participates in the electrochemical reaction process, or in other words, the battery activation process. In addition, it can be seen from the figure that the discharge capacity of Comparative Example 1 is slightly higher than the discharge capacity of the battery of Example 1, but when the battery of Comparative Example 1 is cycled to 60 weeks, the discharge capacity begins to decay. This is because the volume of the metallic lithium negative electrode changes seriously during the cycle, resulting in a large amount of "dead lithium", which in turn rapidly reduces the active lithium of the entire battery and decays the discharge capacity. The battery cycle life of Example 1 using a lithium-free negative electrode is significantly extended. When the cycle reaches 95 weeks, the battery discharge capacity begins to decay.

[0072] Obviously, those skilled in the art can make various changes and modifications to the present disclosure without departing from the spirit and scope of the present disclosure. Thus, if these modifications and variations of the present disclosure fall within the scope of the claims of the present invention and their equivalents, the present disclosure is also intended to include these modifications and variations.

Claims

1. A sulfur positive electrode for a lithium-sulfur battery, characterized in that: The sulfur positive electrode comprises a sulfur positive electrode membrane and an active lithium membrane covering the sulfur positive electrode membrane, wherein the mass of active lithium in the active lithium membrane is 10%-45% of the mass of active sulfur in the sulfur positive electrode membrane.

2. The sulfur cathode according to claim 1, characterized in that The active sulfur in the sulfur positive electrode membrane is elemental sulfur, sulfurized polyacrylonitrile and a combination thereof.

3. The sulfur cathode according to claim 1, characterized in that The sulfur positive electrode membrane also includes a surface-treated carbonaceous carrier material, which is carbon nanotubes, graphene, ordered mesoporous carbon, transition metal carbides and combinations thereof. The surface of the surface-treated carbonaceous carrier material has at least one of the following chemical bonds: CN, CO, CB, CP, CS, CM (M is a metal element, including at least one of Li, Na, Mg, Al, Fe, Ti, K, Ca, Cr, Mn, Co, Ni, Cu, Zn, Zr, Mo, Ag, In, Sn, Au, Pt, W, Pb, Ge), CF, C-Cl, C-Br, CI.

4. The sulfur cathode according to claim 1, characterized in that The active lithium film is a metallic lithium film, and its thickness is 1 micron to 50 microns; Preferably, the metal lithium film has through holes, and a porosity of 1% to 85%.

5. A lithium-sulfur battery, characterized in that: The lithium-sulfur battery comprises: The sulfur cathode according to any one of claims 1 to 4; No lithium anode; and Electrolytes, Among them, the active lithium in the active lithium film reacts with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.

6. The lithium-sulfur battery according to claim 5, characterized in that: The sulfur positive electrode membrane includes a surface-treated carbonaceous carrier material, the Li2S x adsorbed on the carbonaceous support material.

7. The lithium-sulfur battery according to claim 5, characterized in that: The lithium-free negative electrode includes a graphite negative electrode, a silicon-carbon negative electrode or a silicon-oxygen negative electrode; The electrolyte includes a liquid electrolyte and a mixed electrolyte of a liquid electrolyte and a solid electrolyte. The liquid electrolyte comprises a solvent, a lithium salt and optional additives, The solvent is a carbonate solvent and an ether solvent, preferably an ether solvent. The lithium salt is at least one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiBOB (lithium dioxalatoborate), LiDFOB (lithium difluorooxalatoborate), LiFSI (lithium bis(trifluoromethylsulfonyl)imide), LiTFSI (lithium bis(trifluoromethylsulfonyl)imide), LiPF2O2 (lithium difluorophosphate) and LiDTI (lithium 4,5-dicyano-2-trifluoromethylimidazolium). The additives include film formers (including vinylene carbonate, acrylic nitrile, sulfur dioxide, carbon disulfide, fluoroethylene carbonate), flame retardant additives (including trimethylolpropane, triphenyl phosphate, trifluoropropylene, tris(trifluoroethyl) phosphate), charging protective agents (including benzyl alcohol, triethylenediamine), The solid electrolyte includes a sulfide solid electrolyte, an oxide solid electrolyte, an organic solid electrolyte or an organic-inorganic composite solid electrolyte.

8. A method for preparing a lithium-sulfur battery as claimed in any one of claims 5 to 7, comprising: Step 1, preparing a mixture of a sulfur positive electrode active material (active sulfur) and a surface-treated carbonaceous carrier material; Step 2, uniformly mixing the above mixture with a binder, and optionally adding a solvent; Step 3, loading the mixture obtained in step 2 on the surface of the current collector to obtain a sulfur positive electrode membrane; Step 4, loading an active lithium film on the sulfur positive electrode film to obtain a sulfur positive electrode covered with active lithium; Step 5: Assemble the sulfur positive electrode covered with active lithium, the lithium-free negative electrode, the electrolyte, the separator or the solid electrolyte and the packaging materials into a lithium-sulfur battery.

9. The method according to claim 8, characterized in that The active lithium film described in step 4 is loaded on the sulfur positive electrode film by at least one method selected from the group consisting of coating, rolling, physical vapor deposition, and magnetron sputtering.

10. The method according to claim 8, characterized in that The method further comprises reacting the active lithium in the active lithium film with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.